Immune-Enhancing Effects of Co-treatment With Kalopanax pictus Nakai Bark and Nelumbo nucifera Gaertner Leaf Extract in a Cyclophosphamide-Induced Immunosuppressed Rat Model - Park, Young Mi; Lee, Hak Yong; Shin, Dong Yeop; Kim, Dae Sung; Yoo, Jin Joo; Yang, Hye Jeong; Kim, Min Jung; Bae, Jun Sang (Frontiers in Nutrition, 2022)
OBJECTIVE: Immune system disorders can result in various pathological conditions, such as infections and cancer. Identifying therapies that enhance the immune response might be crucial for immunocompromised individuals. Therefore, we assessed the immune-enhancing effect of co-treatment with Kalopanax pictus Nakai Bark and Nelumbo nucifera Gaertner leaf extract (KPNN) in a cyclophosphamide (Cy)-induced immunosuppressed rat model. MATERIALS AND METHODS: For in vitro studies, macrophages and splenocytes were treated with various KPNN doses in the presence or absence of Cy. Macrophage viability, nitric oxide production, splenocyte viability, cytokine production, and natural killer (NK) cell activity were analyzed. For in vivo studies, analysis of weekly body weight, dietary intake, tissue weight, immune-related blood cell count, cytokine levels, and spleen biopsy were performed in a Cy-induced immunocompromised animal model. RESULTS: KPNN significantly increased phospho-nuclear factor-kappa B (NF-κB) and phospho-extracellular-signal regulated kinase (ERK) protein levels and cell viability in macrophages. KPNN significantly increased the NK cell activity in splenocytes compared to that in the control. Cy treatment decreased tumor necrosis factor (TNF)-α, interleukin (IL)-6, and interferon (IFN)-γ production. In the Cy-induced immunosuppression rat model, KPNN-treated rats had significantly higher body and tissue weights than the Cy-treated rats. Additionally, KPNN treatment restored the immune-related factors, such as leukocyte, lymphocyte, and intermediate cell contents, to their normal levels in the blood. The blood cytokines (TNF-α and IL-6) were increased, and spleen tissue damage was significantly alleviated. CONCLUSIONS: Collectively, KPNN exerts an immune-enhancing effect suggesting their potential as an immunostimulatory agent or functional food.